A review of moisture absorption and corrosion resistance performance of FRTP in marine environments - Jiang Lijuan; Wang Xin; Cheng Xiao; Zhou Yinzhi; Yi Yongzhan (Polymer Testing)
Fiber reinforced thermoplastic (FRTP) composites have demonstrated significant potential in marine settings owing to their advantages of light weight, high performance, corrosion resistance and recyclability. However, the long-term performance in marine remains to be verified. This paper summaried the researches on water absorption and corrosion, which are the most significant issues that FRTP faced in marine. Moisture absorption of FRTP is affected by water absorption of each component, incomplete bonding interface, original defects, and so on. Corrosive ions penetrate into FRTP along with water molecules, causing varying degrees of corrosion to the resin, fibers, and interfaces. Both moisture absorption and corrosion significantly reduce the mechanical properties of FRTP. Long-term performance predictions are also introduced, both advantages and disadvantages are discussed. However, all the current predictions carry a degree of uncertainty. Future research should focus on improving preparation techniques and develop efficient prediction models.